Choline transporter-like protein 2 interacts with chitin synthase 1 and is involved in insect cuticle development. - Duan, Y.; Zhu, W.; Zhao, X.; Merzendorfer, H.; Chen, J.; Zou, X.; Yang, Q. (Insect Biochemistry and Molecular Biology, 2022)
Chitin is an aminopolysaccharide present in insects as a major structural component of the cuticle. However, current knowledge on the chitin biosynthetic machinery, especially its constituents and mechanism, is limited. Using three independent binding assays, including co-immunoprecipitation, split-ubiquitin membrane yeast two-hybrid assay, and pull-down assay, we demonstrate that choline transporter-like protein 2 (Ctl2) interacts with krotzkopf verkehrt (kkv) in Drosophila melanogaster. The global knockdown of Ctl2 by RNA interference (RNAi) induced lethality at the larval stage. Tissue-specific RNAi to silence Ctl2 in the tracheal system and in the epidermis of the flies resulted in lethality at the first larval instar. The knockdown of Ctl2 in wings led to shrunken wings containing accumulated fluid. Calcofluor White staining demonstrated reduced chitin content in the first longitudinal vein of Ctl2 knockdown wings. The pro-cuticle, which was thinner compared to wildtype, exhibited a reduced number of chitin laminar layers. Phylogenetic analyses revealed orthologues of Ctl2 in different insect orders with highly conserved domains. Our findings provide new insights into cuticle formation, wherein Ctl2 plays an important role as a chitin-synthase interacting protein.